Limosilactobacillus walteri sp. nov., a novel probiotic antimicrobial lipopeptide-producing bacterium. Issue 1 (16th January 2023) - Saroha, Tanu; Sharma, Shikha; Choksket, Stanzin; Korpole, Suresh; Patil, Prabhu B
Abstract: A Gram-positive facultative anaerobe, nonspore forming, and nonmotile bacterial strain M31 was isolated from faecal contaminated soil. The strain is previously reported to produce a novel antimicrobial lipopeptide and displayed probiotic properties. The strain M31 is catalase negative and fermented d -galactose, d -glucose, esculin, d -maltose, d -lactose, d -melibiose, d -raffinose, d -saccharose (weak reaction), d -xylose (weak reaction), d -ribose (weak reaction), and l -arabinose (weak reaction). The majority of fatty acids were C16:0 (53.9%), C18:0 (26.9%), and C19:0 cyclo ω8c (19.1%). The genome is 2 234 040 bp long with 38.81% guanine-cytosine (GC) content. The pairwise ortho average nucleotide identity and digital DNA-DNA hybridization values of strain M31 with its closest relative species from Limosilactobacillus reuteri clade and Lm. rudii is below the recommended cut-off of 95% and 70%, respectively. Herein, we propose Lm. walteri sp. nov. as a novel species of the genus Limosilactobacillus with M31 = MTCC 12838 = JCM 32759 = KCTC 25569. Abstract : Limosilactobacillus walteri sp. nov. is a novel species of the genus Limosilactobacillus with probiotic potential.